2011
DOI: 10.2337/db10-0409
|View full text |Cite
|
Sign up to set email alerts
|

The Adipocyte-Expressed Forkhead Transcription Factor Foxc2 Regulates Metabolism Through Altered Mitochondrial Function

Abstract: OBJECTIVEPrevious findings demonstrate that enhanced expression of the forkhead transcription factor Foxc2 in adipose tissue leads to a lean and insulin-sensitive phenotype. These findings prompted us to further investigate the role of Foxc2 in the regulation of genes of fundamental importance for metabolism and mitochondrial function.RESEARCH DESIGN AND METHODSThe effects of Foxc2 on expression of genes involved in mitochondriogenesis and mitochondrial function were assessed by quantitative real-time PCR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…It was previously shown that Foxc2 positively controls mitochondrial function and increases PGC1α levels (35), and that Foxo1 and Foxo3A affect lifespan in various multicellular organisms (36). Given that Forkhead factors share a highly conserved forkhead box DNA-binding motif but diverge in their remaining domains, it is conceivable that perhaps Foxc2, in addition to controlling mitochondrial gene programs via the transcriptional regulator TFAM as described previously (38), may regulate PGC1α expression directly through binding of the same forkhead-responsive elements identified here, and that PGC1α levels ultimately may depend on the competition for promoter binding between Foxa3 and Foxc2, exerting opposite effects. Functional assays and gene expression studies will reveal whether Foxc2 is differentially expressed during aging, and whether its function intersects on Foxa3's target promoters.…”
Section: Discussionmentioning
confidence: 83%
“…It was previously shown that Foxc2 positively controls mitochondrial function and increases PGC1α levels (35), and that Foxo1 and Foxo3A affect lifespan in various multicellular organisms (36). Given that Forkhead factors share a highly conserved forkhead box DNA-binding motif but diverge in their remaining domains, it is conceivable that perhaps Foxc2, in addition to controlling mitochondrial gene programs via the transcriptional regulator TFAM as described previously (38), may regulate PGC1α expression directly through binding of the same forkhead-responsive elements identified here, and that PGC1α levels ultimately may depend on the competition for promoter binding between Foxa3 and Foxc2, exerting opposite effects. Functional assays and gene expression studies will reveal whether Foxc2 is differentially expressed during aging, and whether its function intersects on Foxa3's target promoters.…”
Section: Discussionmentioning
confidence: 83%
“…However, a recent study analyzed FOXC2 levels using the T-MTA-6A tissue array and found that this transcription factor overexpresses in the majority of breast cancers and colon cancers, suggesting a role in tumor progression (36). Ectopic expression of FOXC2 in normal adipose tissue induces mitochondrial biogenesis and increases the metabolic capacity of the cells (37). Our proteomic data indicating an enrichment of mitochondrial membrane proteins support a possible hypothesis that the induction of FOXC2 in malignant breast epithelial cells due to increased GPIT expression leads to increased mitochondriogenesis and promotes the growth and expansion of dedifferentiated epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the effects of chronic cold on adipose tissues are recapitulated in mice that have elevated expression of forkhead box protein C2 (Foxc2) in adipocytes 15 . Specifically, Foxc2 increases BAT mass, induces beige fat cell development, drives mitochondrial biogenesis and promotes angiogenesis in fat tissue [82][83][84] . Foxc2 functions in fat cells to a large extent by driving the expression of the R1α regulatory subunit of protein kinase A (PKA, encoded by Prkar1a) 15,85 , thus sensitizing adipocytes to the effects of catecholamines.…”
Section: Sympathetic Nerve Control Of Brown and Beige Fatmentioning
confidence: 99%